2020
DOI: 10.1148/ryct.2020200337
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Chest Radiography Sensitivity for COVID-19: A Multi-Institutional Study in the United States

Abstract: Serial chest radiography sensitivity for detection of novel 2019 coronavirus infection approaches chest CT, suggesting utility of chest radiography as an adjunctive diagnostic tool for COVID-19 patients. ABBREVIATIONS AUC (area under the curve), ROC (receiver operating characteristic curve), COVID-19 (novel coronavirus 2019 infection), COVID-19+ (positive for novel coronavirus 2019 infection), COVID-19-(negative for novel coronavirus 2019 infection), GGO (ground-glass opacity), DA (diffuse airspace opacity), I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 18 publications
2
54
0
4
Order By: Relevance
“…States centres for disease control and prevention and also recommendations given by American college of radiology and the society of thoracic radiology, do not suggest the use of CT and chest radiography for large-scale screening and diagnosis. 3 The sensitivity of chest X-ray (CXR) in COVID-19 detection although is low, up to 18% can have a normal chest radiographs or CT when mild or early in the disease course, this decreases to 3% in severe disease and it is shown that serial CXRs done in these patients has accuracy approaching that of chest CT. 4 The pattern that is highly suggestive of COVID-19 infection, in this current pandemic situation, on a CXR is bilateral "patchy" and/or "confluent, band like" ground glass opacity or consolidation in a peripheral and mid-to-lower lung zone, other patterns that are seen on a chest radiograph include parenchymal abnormalities and pleural effusion, although it is a rare finding. 5 In many patients a baseline CXR done at the time of symptom onset maybe normal, some studies have shown that the severity of findings at chest radiography peaked at 10-12 days from the date of symptom onset.…”
mentioning
confidence: 82%
“…States centres for disease control and prevention and also recommendations given by American college of radiology and the society of thoracic radiology, do not suggest the use of CT and chest radiography for large-scale screening and diagnosis. 3 The sensitivity of chest X-ray (CXR) in COVID-19 detection although is low, up to 18% can have a normal chest radiographs or CT when mild or early in the disease course, this decreases to 3% in severe disease and it is shown that serial CXRs done in these patients has accuracy approaching that of chest CT. 4 The pattern that is highly suggestive of COVID-19 infection, in this current pandemic situation, on a CXR is bilateral "patchy" and/or "confluent, band like" ground glass opacity or consolidation in a peripheral and mid-to-lower lung zone, other patterns that are seen on a chest radiograph include parenchymal abnormalities and pleural effusion, although it is a rare finding. 5 In many patients a baseline CXR done at the time of symptom onset maybe normal, some studies have shown that the severity of findings at chest radiography peaked at 10-12 days from the date of symptom onset.…”
mentioning
confidence: 82%
“…The sensitivity of CXRs depends on the progression of COVID-19 infection. The sensitivity (69%) of CXRs imaging is higher in mild to moderate COVID-19 patients was reported[ 43 ]. Another single-centre study found that 27 patients had a bilateral or unilateral distribution of 32 patients, and 84% had a sensitivity[ 44 ].…”
Section: Radiological Features Of Covid-19mentioning
confidence: 99%
“…CXR generally reveals pure ground glass, mixed ground-glass opacities-consolidation in bilateral peripheral and lower lungs zones[ 11 ]. Specificity and sensitivity of CXR for COVID-19 infection increased with time (sensitivity of 55% at ≤ 2 d increased to 79% at > 11 d) while specificity decreased with time (specificity of 83% decreased to 70%)[ 9 ]. The increase false negative of COVID-19 infection on CXR was found in young age and African-American ethnicity[ 9 ].…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…Specificity and sensitivity of CXR for COVID-19 infection increased with time (sensitivity of 55% at ≤ 2 d increased to 79% at > 11 d) while specificity decreased with time (specificity of 83% decreased to 70%)[ 9 ]. The increase false negative of COVID-19 infection on CXR was found in young age and African-American ethnicity[ 9 ]. When compare to CXR, computer tomography (CT) of the chest in patients with COVID-19 showed higher sensitivity in detecting lung abnormality (CT chest 86.2% vs CXR 49.1%)[ 8 ] (Figure 1 ).…”
Section: Imaging Modalitiesmentioning
confidence: 99%